A Consensus on Minimizing the Risk of Hyaluronic Acid Embolic Visual Loss and Suggestions for Immediate Bedside Management. (6th November 2019) - Goodman, Greg J; Magnusson, Mark R; Callan, Peter; Roberts, Stefania; Hart, Sarah; McDonald, Cara B; Clague, Michael; Rudd, Alice; Bekhor, Philip S; Liew, Steven; Molton, Michael; Wallace, Katy; et al.
Abstract: Background: Hyaluronic acid fillers have a satisfactory safety profile. However, adverse reactions do occur, and rarely intravascular injection may lead to blindness. Currently there is no internationally recognized consensus on the prevention or management of blindness from hyaluronic acid filler. Objectives: The authors sought to give guidance on how to minimize the risk and optimize the management of this rare but catastrophic adverse reaction. Methods: A multinational group of experts in cosmetic injectables from multiple disciplines convened to review current best practice and develop updated consensus recommendations for prevention and bedside intervention if visual loss occurs after cosmetic injection of hyaluronic acid filler. Results: The consensus group provided specific recommendations focusing on the consenting process, prevention, and early management of visual impairment related to intravascular hyaluronic acid filler injection. Conclusions: Although visual loss due to filler injections is rare, it is important that both patient and physician be aware of this risk. In this paper the authors describe methods and techniques available to reduce the risk and also document suggested initial management should a clinician find themselves in this situation. Level of Evidence: 5: